Efektivitas Konseling realita dalam Memantapkan Pilihan Karir Mahasiswa Program Studi Bimbingan dan Konseling - Yusron, Ahmad; Putri, Dessy Ameliani Sasika; Andieni, Vicky Dewi (Psikopedagogia, 2017)
This study aimed to determine the effectiveness of the reality counseling in developing students’ career decision. This was a one group pretest-posttest quasi-experimental study. The subjects of this study were seven students of 2013 Guidance and Counseling department whose score stability was lower than career decision by using a close-ended questionnaire to collect the data. The data analysis technique of this study was paired t-test. Based on the result of this study, it can be concluded that there was a difference in the students’ stability score of career decision. The pre-treatment score was low, while the post-treatment score was high. It was proven by the result of T-test analysis which p = 0.000 < 0.05 and t count 8,280 > t table = 2,447. It can be concluded that the reality counseling was effective to develop career decision. This study is recomended for the university counselor to reinforce students’ career decision through reality counseling.